URBAN AGRICULTURE: A SUSTAINABLE APPROACH TO LAND MANAGEMENT - Elvira, Ade Irma; Pradana, Wiwit Ayu (BULETIN ADALAH, 2025)
Urban agriculture is farming conducted within urban communities and can be utilized as an efficient way to make use of land and natural resources. Urban areas currently consume 80% of the total energy produced globally and contribute over 70% to the total global greenhouse gases (GHGs) emissions. Urban agriculture can implement environmental sustainability by reducing GHG emissions and maintaining the air quality of cities. Various methods such as hydroponics, vertical farming, wall gardening, and aquaponics can be adopted to enhance agricultural productivity within limited urban spaces. Sustainable efforts need comprehensive policies regulating urban agriculture, including expanding household gardens, utilizing environmentally friendly technologies, and fostering stakeholder cooperation for urban agricultural development. This paper aims to highlight the importance of urban agriculture in achieving sustainable land management.